MicroRNA‐122 promotes apoptosis of keratinocytes in oral lichen planus through suppressing VDR expression. Issue 7 (3rd March 2021) - Ge, Xuejun; Xie, Hanting; Wang, Lu; Li, Ran; Zhang, Fang; Xu, Jing; Zhao, Bin; Du, Jie
Abstract: MicroRNA‐122 (miR‐122) is known to be up‐regulated by inflammation to exert a variety of biological functions in hepatocellular carcinoma (HCC)‐derived human cell lines. Vitamin D receptor (VDR) is reported to regulate excessive oral keratinocytes apoptosis which compromises oral epithelial barrier in oral lichen planus (OLP). Although many studies have suggested that miR‐122 is capable of regulating cell apoptosis, its effects on the development of OLP and VDR expression are still unclear. Herein, we demonstrate that miR‐122 expression is increased in the epithelial layer of OLP. Mechanically, transcription factor nuclear factor‐κB (NF‐κB) selectively binds with κB element in the promoter of miR‐122 to accelerate gene transcription. The up‐regulation of miR‐122 induces cell apoptosis in human oral keratinocytes (HOKs) by targeting VDR mRNA. In VDR knockout oral keratinocytes, miR‐122 fails to improve caspase 3 activity and cleaved caspase 3 and poly(ADP‐ribose) polymerase (PARP) levels. Moreover, VDR overexpression is able to reverse lipopolysaccharide (LPS)‐ or activated CD4+ T cell–induced miR‐122 up‐regulation and ameliorate miR‐122‐stimulated caspase 3 activity. Collectively, our results suggest that miR‐122 promotes oral keratinocytes apoptosis in OLP through decreasing VDR expression.